The Circadian Clock Gene Bmal1 Modulates Myometrium Contractile Function in Pregnant Mice - Van Quynh Duong, Thu (J Endocr Soc, 2021)
Caesarian section should be avoided unless medically required. Caesarian section is often a result of failed labor enhancement. While most natural births occur at night, labor enhancement is often scheduled during the day. We propose that the disparity between the commonly used timing of labor enhancement in the clinic, from the timing of natural birth, could contribute to the high rate of labor induction failure. Oxytocin receptor agonists are the most used labor enhancing agents. In pregnant non-human primates, oxytocin enhances uterine contractions more efficiently at night than during the day, suggesting a daily change in uterine sensitivity to oxytocin in pregnancy. To identify the molecular mechanisms generating daily changes in uterine function, we here explore the role of the molecular clock gene, Bmal1 (Brain and muscle ARNTL1-like), in the pregnant mouse myometrium. BMAL1 is a transcription factor required to generated circadian rhythms at the cellular level. We hypothesize that Bmal1 in uterine myometrial cells generates circadian rhythms and establishes the daily change in uterine contractile response to oxytocin. To evaluate circadian rhythms ex vivo, we collected myometrium samples from the validated circadian Per2:luciferase reporter mice at gestation day 17-18. We found that the pregnant mouse myometrium possesses circadian rhythms, which are generated by the molecular clock, as triple transgenic Per2:luciferase mice with Bmal1 conditionally deleted in the myometrium (cKO) do not have rhythmic expression of the Per2:luciferase reporter. To determine if BMAL1 is required to establish uterine contractions, we used a myograph to measure ex vivo uterine contractions at gestation day 17-18. In controls, uterine contraction force was significantly higher at ZT15 (3h after lights OFF) versus ZT3 (3h after lights ON). Interestingly, our preliminary data show increased basal contractile force at ZT15 in cKO as compared to controls. In addition, the cKO uterus contracted stronger to oxytocin than controls. Our findings identify Bmal1 as a clock gene modulating basal contractions in the mouse uterus and indicate Bmal1 might be a regulator of uterine sensitivity to oxytocin. Future work will focus on identifying the molecular mechanisms driven by BMAL1 to regulate uterine function in pregnancy. This work has the potential to provide insights into how we can improve labor enhancing treatment strategies in the clinic in the future.